LN

cho a > 0 ,b>0 va a + b2012 = a2013 + b2013 = a2014 + b2014 . tinh a2015 + b2015

KB
30 tháng 4 2019 lúc 15:29

Ta có : \(a^{2012}+b^{2012}+a^{2014}+b^{2014}=\left(a^{2012}+a^{2014}\right)+\left(b^{2012}+b^{2014}\right)\ge2a^{2013}+2b^{2013}\)

( AD BĐT Cô - si cho a ; b dương ) 

Dấu " = " xảy ra \(\Leftrightarrow a^{2012}=a^{2014};b^{2012}=b^{2014}\) \(\Leftrightarrow a=b=1\left(a,b>0\right)\)

\(\Rightarrow a^{2015}+b^{2015}=1+1=2\)

Bình luận (0)

Các câu hỏi tương tự
LC
Xem chi tiết
NT
Xem chi tiết
TG
Xem chi tiết
DH
Xem chi tiết
H24
Xem chi tiết
NT
Xem chi tiết
H24
Xem chi tiết
C9
Xem chi tiết
CL
Xem chi tiết